Abnormal uterine bleeding in relation to thyroid dysfunction - Sudha, H. C.; Sunanda, K. M.; G. S., Anitha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Abnormal uterine bleeding is an abnormal bleeding from the uterus in absence of any organic disease of genital tract and demonstrable extra genital causes. Thyroid dysfunction is marked by large number of menstrual abnormalities. This study is aimed at detecting thyroid dysfunction in patients with provisional diagnosis of AUB (abnormal uterine bleeding).and refer positive cases to physician for further management. Methods: All patients from are from puberty to pre-menopausal age groups, presenting as menoraghia, metrorragia, polymenorrhoea, polymenorragia, hypomenorrhoea, and acyclical bleeding. Onset, duration, amount of bleeding, complaints related to thyroid dysfunction was noted in detail. A thorough clinical examination including general physical examination, neck examination, systemic and gynecological examination was carried out, with special reference to thyroid dysfunction. A provisional clinical diagnosis of DUB was made. Patients with clinical signs and symptoms of thyroid disease were excluded. All these patients were subjected to routine investigations like Hb%, blood counts, urine routine, and bleeding and clotting time to rule out coagulation defects. Then all were subjected for serum T3, T4, and TSH estimation. Patients were then grouped into 4 categories: euthyroid, subclinical lhypothyroid, hypothyroid, and hyperthyroid. Patients who had thyroid disease, on hormonal treatment, IUCD users, and bleeding disorders were excluded. Results: Among 100 patients studied with abnormal uterine bleeding, patients were distributed according to age groups from puberty to perimenopause age. Majority of patients belongs to 31-40 years of age about 40% and the least age group were between 41-45 years of age.(7%).Among different parity status AUB was more common among para three patients(26%). Out of 100 patients, 32% of patients had thyroid dysfunction of which 16% of patients had subclinical hypothyroidism. 15% of patients had hypothyroidism and only 2% of patients had hyperthyroidism. The commonest bleeding abnormality in AUB were polymenorrhoea (30%) and menorrhagia (35%). All hyperthyroid cases were oligomenorrhoeic. Conclusions: This study concludes that thyroid dysfunction should be considered as an important etiological factor for menstrual abnormality. The biochemical evaluation of T3, T4, and TSH estimations should be made mandatory in AUB cases to detect apparent and occult thyroid dysfunction.